IJLEAL Workshop - Nurkarimah, Yusof (2019)
January 18th, 2019 – Recently, the managing team of The International Journal of Language Education and Applied Linguistics (IJLEAL) has successfully participated in a workshop at Rocana Hotel, Kuantan. IJLEAL is a double blind peer-reviewed, open access scholarly journal which is published twice a year by UMP Publisher. Led by Dr. Hafizoah, IJLEAL Editor-In-Chief, the workshop is designed to unveil and enhance IJLEAL dynamism in its journal management.